Life is lived in moments: And what will be the supreme moment? (Mayéutica Revista Científica de Humanidades y Artes, 2025)
The freedom to write some notes for Mayéutica speaks of the scientific spirit that animates those who today, in the midst of the situation in which we live, fulfill the titanic task, if you will pardon the metaphor, of editing it. Don Quixote said: “Freedom, Sancho, is one of the most precious gifts given to men by the heavens”. Accepting the proposal was an instantaneous decision; that life is full of moments is a truism. Moments of reflection to approach a subject, to have the exact time and the precise space to order the thought to write, to rewrite ideas. But who defines what an instant is?
Keywords: Mayéutica Revista científica de Humanidades y Artes; Editorial